2011
DOI: 10.4317/medoral.16.e348
|View full text |Cite
|
Sign up to set email alerts
|

The development and inflammatory features of radiotherapy-induced glossitis in rats

Abstract: Objectives: To improve the existing animal models (mice, rats, and hamsters) for radiotherapy-induced oral mucositis (RTOM), thereby establishing a radiotherapy-induced glossitis (RTG) Sprague-Dawley (SD) rat model. Study Design: A lead device was designed to limit radiation exposure to a 1×1 cm2 area of a rat's dorsal anterior tongue with a single 30Gy of X-ray radiation. The general conditions of the irradiated rats, such as body-weight and behavior, were observed. The oral mucositis index (OMI) of the RTG r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…It decreased between days 7 and 10 associated with decrease in the amounts of food consumption and water intake, and then gradually recovered to normal (data not shown). Although the delayed occurrence of oral mucositis has been reported in previous studies (Murphy et al, 2008;Mangoni et al, 2009;Li et al, 2011), this is the first report to demonstrate delayed weight loss. The cause of this delayed weight loss is considered to be decreased food consumption as a result of oral mucositis, as food consumption and water intake decreased in parallel with the degree of tongue damage.…”
Section: Establishment Of X-ray Irradiation-induced Glossitis Modelmentioning
confidence: 41%
See 4 more Smart Citations
“…It decreased between days 7 and 10 associated with decrease in the amounts of food consumption and water intake, and then gradually recovered to normal (data not shown). Although the delayed occurrence of oral mucositis has been reported in previous studies (Murphy et al, 2008;Mangoni et al, 2009;Li et al, 2011), this is the first report to demonstrate delayed weight loss. The cause of this delayed weight loss is considered to be decreased food consumption as a result of oral mucositis, as food consumption and water intake decreased in parallel with the degree of tongue damage.…”
Section: Establishment Of X-ray Irradiation-induced Glossitis Modelmentioning
confidence: 41%
“…The timing to appearance of ulceration following radiation exposure should be associated with the cell cycle of lingual epithelial cells (Vissink et al, 2003), in which X-ray irradiation-induced DNA damage arrests cell proliferation. In the previous study of Li et al (2011), the maximal glossitis score was observed 14 days after irradiation, related to the fusion of pre-existing ulcers. The discrepancy in timing of ulceration between the current study and previous study might be due to differences in dosage and techniques of X-ray exposure.…”
Section: Establishment Of X-ray Irradiation-induced Glossitis Modelmentioning
confidence: 82%
See 3 more Smart Citations